Electrochemical studies of CNT/Si–SnSb nanoparticles for lithium ion batteries. (October 2015) - Nithyadharseni, P.; Reddy, M.V.; Nalini, B.; Ravindran, T.R.; Pillai, B.C.; Kalpana, M.; Chowdari, B.V.R.
Graphical abstract: Highlights: Si added SnSb and CNT exhibits very low particle size of below 30 nm A strong PL quenching due to the addition of Si to SnSb. Electrochemical studies show CNT added SnSb shows good capacity retention. Abstract: Nano-structured SnSb, SnSb–CNT, Si–SnSb and Si–SnSb–CNT alloys were synthesized from metal chlorides of Sn, Sb and Si via reductive co-precipitation technique using NaBH4 as reducing agent. The as prepared compounds were characterized by various techniques such as X-ray diffraction (XRD), scanning electron microscope (SEM), Raman, Fourier transform infra-red (FTIR) and photoluminescence (PL) spectroscopy. The electrochemical performances of the compounds were characterized by galvanostatic cycling (GC) and cyclic voltammetry (CV). The Si–SnSb–CNT compound shows a high reversible capacity of 1200 mAh g −1 . However, the rapid capacity fading was observed during cycling. In contrast, SnSb–CNT compound showed a high reversible capacity of 568 mAh g −1 at 30th cycles with good cycling stability. The improved reversible capacity and cyclic performance of the SnSb–CNT compound could be attributed to the nanosacle dimension of SnSb particles and the structural advantage of CNTs.